Degradation behavior of ionic‐covalent entanglement hydrogels. Issue 1 (22nd July 2014) - De Silva, D. Awanthi; Martens, Penny J.; Gilmore, Kerry J.; in het Panhuis, Marc
ABSTRACT Ionic‐covalent entanglement (ICE) hydrogels are a recently introduced new type of robust materials for potential future application in the fields of tissue engineering and soft robotics. Here the degradation behavior of gellan gum/polyacrylamide ICE hydrogels immersed in PBS or enzyme solutions is presented. It is demonstrated that ICE gels immersed in enzymes became stiffer, whereas under cyclic testing their mechanical responses stabilize after 10 loading/unloading cycles whether immersed in PBS or enzyme solutions. The leachates of the ICE hydrogels were found to be non‐cytotoxic for the growth of L929 and PC12 cells. These findings will be of benefit to the future development of tissue engineering applications based on these gel materials. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41216.